Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.22743
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DYRK1B suppresses the proliferation and migration of liposarcoma cells

Abstract: Liposarcoma is a common subtype of soft tissue sarcoma and accounts for 20% of all sarcomas. Conventional chemotherapeutic agents have limited efficacy in liposarcoma patients. Expression and activation of serine/threonine-protein kinase dual-specificity tyrosine-(Y)-phosphorylation regulated kinase 1B (DYRK1B) is associated with growth and survival of many types of cancer cells. However, the role of DYRK1B in liposarcoma remains unknown. In this study, we investigated the functional and therapeutic relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The first studies into the influence of DYRK1B in cancer suggested a role in the survival of cancer cells, with a stronger DYRK1B expression in CRC samples than in normal tissue [ 95 ]. Several studies extended this finding to other tumor types, included liposarcoma [ 96 ], rhabdomyosarcoma [ 97 ], osteosarcoma [ 98 ], lung [ 99 ], breast [ 100 ], ovary [ 101 ] and PDAC [ 68 , 102 , 103 ]. Indeed, a differential expression analysis using TCGA data finds DYRK1B to be overexpressed in several tumor types, including bladder (BLCA); breast (BRCA); kidney (KICH, KIRC and KIRP); liver (LIHC); prostate (PRAD); thyroid (THCA) and uterus (UCEC) ( Table S1 ).…”
Section: Dyrk1bmentioning
confidence: 95%
See 1 more Smart Citation
“…The first studies into the influence of DYRK1B in cancer suggested a role in the survival of cancer cells, with a stronger DYRK1B expression in CRC samples than in normal tissue [ 95 ]. Several studies extended this finding to other tumor types, included liposarcoma [ 96 ], rhabdomyosarcoma [ 97 ], osteosarcoma [ 98 ], lung [ 99 ], breast [ 100 ], ovary [ 101 ] and PDAC [ 68 , 102 , 103 ]. Indeed, a differential expression analysis using TCGA data finds DYRK1B to be overexpressed in several tumor types, including bladder (BLCA); breast (BRCA); kidney (KICH, KIRC and KIRP); liver (LIHC); prostate (PRAD); thyroid (THCA) and uterus (UCEC) ( Table S1 ).…”
Section: Dyrk1bmentioning
confidence: 95%
“…The latter would enhance the effectiveness of other antiproliferative drugs in combinatorial approaches. For instance, the DYRK1B inhibitor AZ191 [ 52 ] increases the anticancer effects of doxorubicin in liposarcoma cell lines [ 96 ] or sensitizes the PDAC cell lines to mTOR inhibition [ 115 ]. However, AZ191 has been also shown to counteract the antitumor effects of the lysosome inhibitor Bafilomycin A1 in HCC cell lines [ 111 ].…”
Section: Dyrk Inhibitors As Antitumor Therapiesmentioning
confidence: 99%
“…The human DYRK1B gene is located on chromosome 19q13.2, a region often amplified in ovarian and pancreatic cancer[ 37 - 42 ]. DYRK1B is especially highly expressed in colon carcinoma[ 36 , 43 , 44 ], prostate carcinoma[ 24 , 45 - 47 ], lung cancer[ 45 ], pancreatic ductal adenocarcinomas[ 37 , 48 - 52 ], rhabdo-myosarcomas[ 53 ], osteosarcoma[ 54 ], and liposarcoma[ 55 ]. Also, overexpression of DYRK1B has been reported in breast cancer[ 56 - 58 ], cervical cancer[ 59 , 60 ], and mela-noma[ 61 , 62 ].…”
Section: Dyrk1b Expression Intracellular Localization and Upstream mentioning
confidence: 99%
“…As we have discussed above, DYRKs comprise a family of kinases which are key regulators of signal transduction, cell proliferation, survival, and differentiation[ 18 ]. In particular, DYRK1B is a multifunctional dual-specificity kinase involved in cell cycle progression, differentiation and cell viability[ 42 , 69 , 70 ], and plays key roles in a variety of physiological developmental processes during myogenesis[ 69 , 70 , 74 ], spermatogenesis[ 77 ], neurogenesis[ 35 ] and cell motility[ 55 ], as well as in as in human diseases, such as cancer[ 24 , 36 , 39 , 41 , 50 ] and metabolic syndrome[ 76 ].…”
Section: Molecular Mechanisms Of Dyrk1b Function In Development and Hmentioning
confidence: 99%
See 1 more Smart Citation